A polyurethane acrylate elastomer, a method for preparing the same, and an application thereof

CN116948205BActive Publication Date: 2026-10-23XIAN THERMAL POWER RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311067588.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2026-10-23
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

[0005]针对现有技术中存在的技术问题,本发明提供了一种聚氨酯丙烯酸酯弹性体及其制备方法和应用,以解决现有的金属配位自修复聚氨酯弹性体体系的拉伸断裂强度太低,不足以满足工程应用;其次,其中的二硫键在受热、紫外光照射和氧化还原条件下,能引发链交换反应,自修复所需的温度太高,限制了实际应用的技术问题

Benefits of technology

[0027]本发明提供了一种聚氨酯丙烯酸酯弹性体及其制备方法和应用,利用可逆加成-断裂链转移自由基聚合(RAFT)方法,以使聚合物分子质量分布更加趋于均衡,有助于输出可靠持续的产品性能;其次,向聚合物中引入双硫键(动态共价键)在可见光照射下可均裂为硫自由基,在硫自由基重新生成双硫键的过程中实现链段的重组;同时,利用卟啉大环中,四个氮原子构成了一定空间位置和配位能力的环境,与金属离子形成稳定的配合物,再加上聚氨酯本身具有氢键作用,形成强金属配位键与弱氢键作用相结合构成的高动态性质的交联网络,大大提高了聚合物弹性体的自修复效率,进而实现对聚合物裂纹的修复;最后,将功能化改性的多壁碳纳米管直接共聚到聚合物分子链上,与传统掺杂或物理共混的方式相比,以化学键的形式保证了材料不发生相分离,稳定性高,极大的提高了材料的力学强度;所述聚氨酯丙烯酸酯弹性体具有制备过程简单、分子量可控、优异的力学强度和韧性以及自修复的特点,将所述弹性体材料作为自愈性可拉伸的导电器件,在表面镀层保护、生物医药材料、柔性可穿戴电子、锂电池以及航空航天等领域具有潜在的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004410041930000121
    Figure BDA0004410041930000121
  • Figure BDA0004410041930000131
    Figure BDA0004410041930000131
Patent Text Reader

Abstract

The application discloses a polyurethane acrylate elastomer and a preparation method and application thereof, and relates to the technical field of elastomers, in particular to a polyurethane acrylate elastomer, a preparation method and application thereof. The polyurethane acrylate elastomer is prepared by the following steps: esterification reaction of carboxylated multi-walled carbon nanotubes and hydroxypropyl acrylate to obtain double bond functionalized modified multi-walled carbon nanotubes; nucleophilic addition reaction of diisocyanate monomers and polyglycol monomers, and then addition of hydroxyethyl acrylate to introduce double bonds, so as to obtain double bond terminated polyurethane emulsion; reversible addition-fragmentation chain transfer radical polymerization of the double bond terminated polyurethane emulsion, butyl acrylate and the double bond functionalized modified multi-walled carbon nanotubes to obtain multi-walled carbon nanotube modified polyurethane acrylate emulsion; introduction of coordinated metal ions into the multi-walled carbon nanotube modified polyurethane acrylate emulsion, and drying to obtain the polyurethane acrylate elastomer. The polyurethane acrylate elastomer has the characteristics of controllable molecular weight, excellent mechanical strength and toughness and self-repairing, and has potential application prospect as a self-healing stretchable conductive device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer material synthesis technology, and specifically relates to a polyurethane acrylate elastomer, its preparation method and application. Background Technology

[0002] Self-healing elastomers, as a type of smart material, can repair cracks or localized damage caused by external forces during use, thereby restoring their original function and extending their service life. Polyurethane acrylate (PUA) contains acrylic functional groups and urethane bonds. The cured polymer has the high wear resistance, adhesion, flexibility, high peel strength, and excellent low-temperature resistance of polyurethane, as well as the excellent optical properties and weather resistance of polyacrylate. It is a radiation-cured material with excellent comprehensive performance and is widely used in coatings, adhesives, plastics, synthetic fibers, coated fibers, and other fields.

[0003] Currently, the common approach is to introduce metal coordination bonds into the polyurethane acrylate network to form a metal-coordinated self-healing polyurethane elastomer system. In this system, hydrogen bonds can be balanced, whether at the ends of the polymer chains or as dangling groups, thereby regulating the mechanical and self-healing properties of the polymer. However, the main problems with existing metal-coordinated self-healing polyurethane elastomer systems are: the tensile strength of the elastomer is too low to meet engineering applications; secondly, the disulfide bonds can initiate chain exchange reactions under heating, ultraviolet light irradiation, and redox conditions, requiring excessively high temperatures for self-healing, which limits practical applications.

[0004] Therefore, there is an urgent need to develop a new polyurethane acrylate elastomer that has high mechanical strength and toughness while also possessing self-healing properties. Summary of the Invention

[0005] To address the technical problems existing in the prior art, this invention provides a polyurethane acrylate elastomer, its preparation method, and its application, in order to solve the problem that the tensile fracture strength of the existing metal-coordinated self-healing polyurethane elastomer system is too low to meet engineering applications; secondly, the disulfide bonds in it can initiate chain exchange reactions under heating, ultraviolet light irradiation, and redox conditions, and the temperature required for self-healing is too high, which limits the technical problems of practical application.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] This invention provides a method for preparing a polyurethane acrylate elastomer, comprising:

[0008] Carboxylated multi-walled carbon nanotubes were esterified with hydroxypropyl acrylate to obtain grafted double bond functionalized multi-walled carbon nanotubes.

[0009] A polyurethane emulsion with double bond end capping was obtained by nucleophilic addition reaction of diisocyanate monomer and polydiol monomer, followed by addition of hydroxyethyl acrylate to introduce double bonds.

[0010] Using the double-bond-terminated polyurethane emulsion, butyl acrylate, and the grafted double-bond functionalized multi-walled carbon nanotubes, a multi-walled carbon nanotube-modified polyurethane acrylate emulsion was obtained by reversible addition-bond-fracture transfer radical polymerization.

[0011] Coordinated metal ions are introduced into the polyurethane acrylate emulsion modified with multi-walled carbon nanotubes, and then dried to obtain the polyurethane acrylate elastomer.

[0012] Furthermore, the process of esterifying carboxylated multi-walled carbon nanotubes with hydroxypropyl acrylate to obtain grafted double-bond functionalized multi-walled carbon nanotubes is as follows:

[0013] Carboxylated multi-walled carbon nanotubes, hydroxypropyl acrylate, hydroquinone, anhydrous sodium sulfate, and methyl isoamyl ketone were ultrasonicated at room temperature under nitrogen protection; then the temperature was raised to a preset temperature and stirred at that preset temperature; then anhydrous ethanol was added for dilution, and the mixture was filtered to obtain a filter cake; the filter cake was washed and dried to obtain the grafted double bond functionalized multi-walled carbon nanotubes.

[0014] Furthermore, the mass ratio of carboxylated multi-walled carbon nanotubes, hydroxypropyl acrylate, hydroquinone, anhydrous sodium sulfate, and methyl isoamyl ketone is (5-8):(20-30):(0.5-1):(10-15):(40-50).

[0015] Furthermore, the process of using a diisocyanate monomer to undergo a nucleophilic addition reaction with a polydiol monomer, followed by the addition of hydroxyethyl acrylate to introduce double bonds, to obtain a double-bonded polyurethane emulsion is as follows:

[0016] Diisocyanate monomer, polydiol monomer and organic solvent are mixed, and dibutyltin dilaurate is added to react. Then chain extender and crosslinking agent are added to react. After that, organic solvent and hydroxyethyl acrylate are added to obtain the double bond-terminated polyurethane emulsion.

[0017] Furthermore, the diisocyanate monomer is one of isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the polydiol monomer is one of polycaprolactone diol, polytetrahydrofuran ether diol, and poly(1- and 4-butanediol adipate diol); the chain extender is one of diethylthiuram dihydroxydisulfide and bis(2-hydroxyethyl) disulfide; and the crosslinking agent is one of 5,10,15,20-tetra(4-hydroxyphenyl)porphyrin and 5,10,15,20-tetra(4-aminophenyl)porphyrin.

[0018] Furthermore, the process of obtaining a multi-walled carbon nanotube-modified polyurethane acrylate emulsion via reversible addition-bond-fragmentation transfer radical polymerization using the double-bond-terminated polyurethane emulsion, butyl acrylate, and the grafted double-bond functionalized multi-walled carbon nanotubes is as follows:

[0019] The double-bond-terminated polyurethane emulsion, butyl acrylate, the grafted double-bond functionalized multi-walled carbon nanotubes, and an organic solvent are mixed evenly. Then, RAFT chain transfer agent is added and the mixture is stirred and reacted. The mixture is kept warm and cooled to room temperature before being discharged to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion.

[0020] Furthermore, the process of introducing coordinated metal ions into the multi-walled carbon nanotube-modified polyurethane acrylate emulsion and drying it to obtain the polyurethane acrylate elastomer is as follows:

[0021] An ethanol solution of metal ions is mixed with the polyurethane acrylate emulsion modified with multi-walled carbon nanotubes, and the mixture is stirred continuously to obtain a self-healing elastomer emulsion. The self-healing elastomer emulsion is then dried to obtain the polyurethane acrylate elastomer.

[0022] Furthermore, the metal ion is one of iron ions, nickel ions, copper ions, cobalt ions, manganese ions, and zinc ions.

[0023] The present invention also provides a polyurethane acrylate elastomer, which is prepared by the aforementioned method for preparing a polyurethane acrylate elastomer;

[0024] The polyurethane acrylate elastomer has a molecular weight of 62,820–64,430. When the thin-film polyurethane acrylate elastomer breaks, it can achieve a self-healing efficiency of 85.2%–86.8% under visible light irradiation for 12–24 hours and 100% under ultraviolet light irradiation for 0.5–1 hour. The tensile strength of the polyurethane acrylate elastomer is 46.6–58.6 MPa, and the elongation at break is 1263%–1585%.

[0025] The present invention also provides an application of polyurethane acrylate elastomer as a self-healing stretchable conductive device.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] This invention provides a polyurethane acrylate elastomer, its preparation method, and its applications. It utilizes a reversible addition-fragmentation chain transfer radical polymerization (RAFT) method to achieve a more balanced polymer molecular weight distribution, contributing to reliable and consistent product performance. Secondly, the introduction of disulfide bonds (dynamic covalent bonds) into the polymer allows for homolytic cleavage into sulfur radicals under visible light irradiation, enabling chain segment recombination during the regeneration of disulfide bonds. Simultaneously, the four nitrogen atoms in the porphyrin macrocycle create a specific spatial position and coordination environment, forming stable complexes with metal ions. Combined with the hydrogen bonding inherent in polyurethane, this results in a highly dynamic product characterized by a combination of strong metal coordination bonds and weak hydrogen bonding. The high-quality cross-linked network significantly improves the self-healing efficiency of the polymer elastomer, thereby enabling the repair of polymer cracks. Finally, functionalized modified multi-walled carbon nanotubes are directly copolymerized onto the polymer molecular chain. Compared with traditional doping or physical blending methods, this method ensures that the material does not undergo phase separation through chemical bonds, resulting in high stability and greatly improving the material's mechanical strength. The polyurethane acrylate elastomer has the characteristics of simple preparation process, controllable molecular weight, excellent mechanical strength and toughness, and self-healing. Using this elastomer material as a self-healing, stretchable conductive device has potential applications in fields such as surface coating protection, biomedical materials, flexible wearable electronics, lithium batteries, and aerospace. Detailed Implementation

[0028] To make the technical problems solved by the present invention, the technical solutions, and the beneficial effects clearer, the following specific embodiments provide a further detailed description of the present invention. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of the invention.

[0029] This invention provides a method for preparing a polyurethane acrylate elastomer, comprising: esterifying carboxylated multi-walled carbon nanotubes with hydroxypropyl acrylate to obtain grafted double-bond functionalized multi-walled carbon nanotubes; performing a nucleophilic addition reaction between a diisocyanate monomer and a polydiol monomer, followed by adding hydroxyethyl acrylate to introduce double bonds, to obtain a double-bond-terminated polyurethane emulsion; reversibly performing addition-bond-splitting free radical polymerization on the double-bond-terminated polyurethane emulsion, butyl acrylate, and the grafted double-bond functionalized multi-walled carbon nanotubes to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion; introducing coordinated metal ions into the multi-walled carbon nanotube-modified polyurethane acrylate emulsion, and drying to obtain the polyurethane acrylate elastomer.

[0030] Specifically, the preparation method includes the following steps:

[0031] Step 1: Carboxylated multi-walled carbon nanotubes, hydroxypropyl acrylate, hydroquinone, anhydrous sodium sulfate, and methyl isoamyl ketone are mixed in a mass ratio of (5-8):(20-30):(0.5-1):(10-15):(40-50). The mixture is then sonicated at room temperature under nitrogen protection, followed by heating to a preset temperature and constant-temperature stirring. Anhydrous ethanol is then added for dilution, and the mixture is filtered through a filter membrane to obtain a filter cake. The filter cake is washed with deionized water and dried to obtain grafted double-bond functionalized multi-walled carbon nanotubes.

[0032] In step 1, during room temperature ultrasound, the ultrasound power is 80–100 kHz, and the ultrasound time is 0.5–1.0 h; preferably, the preset temperature is 100 °C, and the constant temperature stirring time is 24 h; when adding anhydrous ethanol for dilution, the mass ratio of carboxylated multi-walled carbon nanotubes to anhydrous ethanol is (5–8):(100–150); the filter membrane is made of polyvinylidene fluoride with a pore size of 0.22 μm; preferably, the washing is performed three times; the drying is performed by vacuum drying; preferably, the vacuum drying temperature is 50 °C, and the time is 24 h.

[0033] Step 2: According to the mass fraction, 17-25 parts of dried diisocyanate monomer, 21-45 parts of polydiol monomer, and 25-35 parts of organic solvent are mixed evenly under nitrogen protection and at 80°C; then 0.1-0.5 parts of dibutyltin dilaurate are added and reacted for 0.5-1 h; after the reaction, 1.5-2.1 parts of chain extender are added and reacted for 0.5-1 h, then 0.7-1.0 parts of crosslinking agent are added and reacted for 0.5-1 h; then, the reaction is kept at a constant temperature for 2-3 h, cooled to 60°C, 28-40 parts of organic solvent are added, and 3.6-7.5 parts of hydroxyethyl acrylate are added to obtain a double-bond-terminated polyurethane emulsion.

[0034] In step 2, the diisocyanate monomer is one of isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the polydiol monomer is one of polycaprolactone diol, polytetrahydrofuran ether diol, and poly(1- and 4-butanediol adipate diol); the chain extender is one of diethylthiuram dihydroxydisulfide and bis(2-hydroxyethyl) disulfide; and the crosslinking agent is one of 5,10,15,20-tetra(4-hydroxyphenyl)porphyrin and 5,10,15,20-tetra(4-aminophenyl)porphyrin.

[0035] Step 3: According to the mass fractions, 32-38 parts of the double-bond-terminated polyurethane emulsion, 4.6-5.9 parts of butyl acrylate, 3.5-4.8 parts of the grafted double-bond functionalized multi-walled carbon nanotubes, and 21-25 parts of organic solvent are stirred and mixed evenly under nitrogen protection. 12-15 parts of RAFT chain transfer agent dissolved in the organic solvent are added dropwise. The mixture is stirred and reacted at 60-70°C for 2-3 hours, kept at this temperature for 4 hours, and then cooled to room temperature before being discharged to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion. The RAFT chain transfer agent is one of 2-cyanoisopropyl dithiobenzoate, allyl pyrrolidine dithiocarbamate, or 2-methyl-2-[(dodecylthiocarbamate)thio]propionic acid. Preferably, the mass fraction of the RAFT chain transfer agent dissolved in the organic solvent is 1%.

[0036] It should be noted that the organic solvent mentioned in steps 2 and 3 is one of chloroform, ethyl acetate, butyl acetate, toluene, acetone, tetrahydrofuran, xylene, and cyclohexanone.

[0037] Step 4: According to the mass fraction, mix 25-30 parts of an ethanol solution with a concentration of 100 mg / L metal ions with 20-25 parts of the multi-walled carbon nanotube modified polyurethane acrylate emulsion, and stir continuously at room temperature for 24 hours to obtain a self-healing elastomer emulsion with interaction between metal coordination bonds and dynamic covalent bonds; wherein the metal ions are one of iron ions, nickel ions, copper ions, cobalt ions, manganese ions and zinc ions.

[0038] Step 5: Pour the self-healing elastomer solution with metal coordination bonds and dynamic covalent bonds into a polytetrafluoroethylene film mold, dry at room temperature for 3 days, and then use a vacuum pump coating machine to lay the viscous product into a film to obtain a smooth and flat film, which is the self-healing elastomer film with metal coordination bonds and dynamic covalent bonds; wherein, the self-healing elastomer film with metal coordination bonds and dynamic covalent bonds is the polyurethane acrylate elastomer.

[0039] Preparation principle:

[0040] The method for preparing polyurethane acrylate elastomers according to the present invention utilizes the esterification reaction of carboxylated multi-walled carbon nanotubes and hydroxypropyl acrylate. Since the carboxylated carbon nanotubes contain a large number of carboxyl groups and hydroxypropyl acrylate contains hydroxyl groups, the carboxyl groups and hydroxyl groups combine to generate water during the esterification reaction, and the esterification reaction is reversible. By adding anhydrous sodium sulfate, the water generated by the combination of carboxyl and hydroxyl groups is absorbed, ensuring the esterification reaction proceeds in the forward direction, thereby obtaining grafted double-bond functionalized multi-walled carbon nanotubes. Furthermore, by adding hydroquinone as a polymerization inhibitor, self-polymerization of hydroxypropyl acrylate and grafted double-bond functionalized multi-walled carbon nanotubes under high-temperature conditions is avoided, as is copolymerization between hydroxypropyl acrylate and the grafted double-bond functionalized multi-walled carbon nanotubes.

[0041] Secondly, the diisocyanate monomer contains isocyanate groups, which can undergo nucleophilic addition with the terminal hydroxyl groups in the polydiol monomer to form urethane, thus obtaining the polyurethane prepolymer. By adding dibutyltin dilaurate as a catalyst, the rate of the nucleophilic addition reaction is effectively increased. A chain extender containing hydroxyl and disulfide bonds is added to introduce disulfide bonds into the polyurethane prepolymer molecular chain, thereby increasing the molecular weight of the polyurethane prepolymer. A porphyrin crosslinking agent containing hydroxyl or amino groups can react with the isocyanate groups, thereby forming a crosslinked network structure in the polyurethane prepolymer molecular chain. At the same time, porphyrin ligands are introduced into the polyurethane prepolymer molecular chain. The hydroxyl groups in hydroxyethyl acrylate react with the isocyanate groups to introduce double bonds into the polyurethane prepolymer molecular chain segments, obtaining a polyurethane emulsion with double bond ends.

[0042] By utilizing double-bond-terminated polyurethane emulsions, grafted double-bond multi-walled carbon nanotubes, and butyl acrylate, reversible addition-fragmentation chain transfer radical polymerization was carried out under the action of RAFT reagent, the degree of polymerization of the polymerization reaction was effectively controlled, resulting in polyurethane acrylates containing multi-walled carbon nanotubes, disulfide bonds, and porphyrin ligands with a narrower molecular weight distribution. In addition, the porphyrin ligands in the polyurethane acrylates containing multi-walled carbon nanotubes, disulfide bonds, and porphyrin ligands chelate with coordinating metal ions, ultimately forming metal coordination bonds on the polyurethane acrylate molecular chain segments.

[0043] The polyurethane acrylate elastomer prepared using the method described in this invention possesses controllable molecular weight, excellent mechanical strength and toughness, and self-healing properties. This elastomer material, as a self-healing, stretchable conductive device, has potential applications in surface coating protection, biomedical materials, flexible wearable electronics, lithium batteries, and aerospace. The molecular weight of the polyurethane acrylate elastomer is 62820–64430. When the thin-film polyurethane acrylate elastomer breaks, it achieves a self-healing efficiency of 85%–90% under visible light irradiation for 12–24 hours and 100% under ultraviolet light irradiation for 0.5–1 hour. The tensile strength of the polyurethane acrylate elastomer is 46.6–58.6 MPa, and the elongation at break is 1263%–1585%.

[0044] Example 1

[0045] This embodiment 1 provides a method for preparing a polyurethane acrylate elastomer, including the following steps:

[0046] Step 1: 5.2g of carboxylated multi-walled carbon nanotubes, 21.6g of hydroxypropyl acrylate, 0.54g of hydroquinone, 11g of anhydrous sodium sulfate, and 41.6g of methyl isoamyl ketone were sonicated at room temperature and 82kHz for 0.52h under N2 protection. Then, the temperature was raised to 100℃ and stirred at a constant temperature for 24h. 106g of anhydrous ethanol was added for dilution. The mixture was filtered through a 0.22μm polyvinylidene fluoride filter membrane. The filter cake was washed three times with deionized water. The resulting filter cake was vacuum dried at 50℃ for 24h to obtain grafted double bond functionalized multi-walled carbon nanotubes.

[0047] Step 2: 17.8g of dried isophorone diisocyanate, 21.8g of polycaprolactone diol monomer, and 25.9g of ethyl acetate were mixed evenly at 80℃ under N2 protection. 0.2g of dibutyltin dilaurate was added and reacted for 0.6h, followed by the addition of 1.7g and another 0.6h. Then, 0.78g of 5,10,15,20-tetra(4-hydroxyphenyl)porphyrin was added and reacted for 0.6h. The reaction was maintained at this temperature for 2.2h, then cooled to 60℃. 30g of ethyl acetate and 3.9g of hydroxyethyl acrylate were added to obtain a double-bond-terminated polyurethane emulsion.

[0048] Step 3: Mix 32.8g of double-bond-terminated polyurethane solution, 4.9g of butyl acrylate, 3.8g of grafted double-bond functionalized multi-walled carbon nanotubes, and 22g of ethyl acetate under N2 protection. Add 1% dithiobenzoic acid-2-cyanoisopropyl ester dissolved in 12.5g of ethyl acetate dropwise. Stir and react at 63℃ for 2.2h, keep warm for 4h, cool to room temperature and discharge to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion.

[0049] Step 4: 25.7g of ethanol solution containing 100mg / L iron ions and 21g of polyurethane acrylate emulsion modified with multi-walled carbon nanotubes were continuously stirred at room temperature for 24h to obtain a self-healing elastomer emulsion with interaction between metal coordination bonds and dynamic covalent bonds.

[0050] Step 5: Pour the self-healing elastomer solution with metal coordination bonds and dynamic covalent bonds into a polytetrafluoroethylene film mold, dry at room temperature for 3 days, and then use a vacuum pump coating machine to lay the viscous product into a film to obtain a smooth and flat film, which is the polyurethane acrylate elastomer.

[0051] Example 2

[0052] This embodiment 2 provides a method for preparing a polyurethane acrylate elastomer, including the following steps:

[0053] Step 1: 6.4g of carboxylated multi-walled carbon nanotubes, 24.6g of hydroxypropyl acrylate, 0.69g of hydroquinone, 13g of anhydrous sodium sulfate, and 44.8g of methyl isoamyl ketone were ultrasonicated at room temperature and 89kHz for 0.7h under N2 protection. Then, the temperature was raised to 100℃ and stirred at a constant temperature for 24h. 120g of anhydrous ethanol was added for dilution. The mixture was filtered through a 0.22μm polyvinylidene fluoride filter membrane. The filter cake was washed three times with deionized water. The resulting filter cake was vacuum dried at 50℃ for 24h to obtain grafted double bond functionalized multi-walled carbon nanotubes.

[0054] Step 2: Mix 20g of dried toluene diisocyanate, 30g of polytetrahydrofuran ether diol monomer, and 29g of chloroform at 80°C under N2 protection. Add 0.3g of dibutyltin dilaurate and react for 0.7h. Add 1.9g of diethylthiuram dihydroxydisulfide and react for 0.7h. Then add 0.83g of 5,10,15,20-tetra(4-hydroxyphenyl)porphyrin and react for 0.7h. Keep the reaction at this temperature for 2.5h. Cool to 60°C, add 34g of chloroform, and add 4.7g of hydroxyethyl acrylate to obtain a polyurethane emulsion with double bonds capped.

[0055] Step 3: Mix 34.8g of double-bond-terminated polyurethane solution, 5.2g of butyl acrylate, 4.2g of grafted double-bond functionalized multi-walled carbon nanotubes, and 23g of chloroform under N2 protection. Add 13.4g of 1% pyrrolidine dithiocarbamate dissolved in chloroform dropwise. Stir and react at 65℃ for 2.4h, keep warm for 4h, cool to room temperature and discharge to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion.

[0056] Step 4: 26.8g of ethanol solution containing 100mg / L nickel ions and 22g of polyurethane acrylate emulsion modified with multi-walled carbon nanotubes were continuously stirred at room temperature for 24h to obtain a self-healing elastomer emulsion with interaction between metal coordination bonds and dynamic covalent bonds.

[0057] Step 5: Pour the self-healing elastomer solution with metal coordination bonds and dynamic covalent bonds into a polytetrafluoroethylene film mold, dry at room temperature for 3 days, and then use a vacuum pump coating machine to lay the viscous product into a film to obtain a smooth and flat film, which is the polyurethane acrylate elastomer.

[0058] Example 3

[0059] This embodiment 3 provides a method for preparing a polyurethane acrylate elastomer, including the following steps:

[0060] Step 1: 7.2g of carboxylated multi-walled carbon nanotubes, 27.6g of hydroxypropyl acrylate, 0.82g of hydroquinone, 14g of anhydrous sodium sulfate, and 47.8g of methyl isoamyl ketone were ultrasonically sonicated at room temperature and 92kHz for 0.8h under N2 protection. Then, the temperature was raised to 100℃ and stirred at a constant temperature for 24h. 130g of anhydrous ethanol was added for dilution. The mixture was filtered through a 0.22μm polyvinylidene fluoride filter membrane. The filter cake was washed three times with deionized water. The resulting filter cake was vacuum dried at 50℃ for 24h to obtain grafted double bond functionalized multi-walled carbon nanotubes.

[0061] Step 2: 22g of dried diphenylmethane diisocyanate, 40g of 1,4-butanediol adipic acid ester monomer and 32g of cyclohexanone were mixed evenly at 80°C under N2 protection. 0.4g of dibutyltin dilaurate was added and reacted for 0.8h. 2.0g of bis(2-hydroxyethyl) disulfide was added and reacted for 0.8h. Then 0.9g of 5,10,15,20-tetra(4-aminophenyl)porphyrin was added and reacted for 0.8h. The reaction was kept at this temperature for 2.7h. The temperature was then lowered to 60°C, 36g of cyclohexanone was added, and 6.2g of hydroxyethyl acrylate was added to obtain a polyurethane emulsion with double bonds capped.

[0062] Step 3: Mix 36.2g of double-bond-terminated polyurethane solution, 5.5g of butyl acrylate, 4.5g of grafted double-bond functionalized multi-walled carbon nanotubes and 24g of cyclohexanone under N2 protection. Add 14.2g of 1% 2-methyl-2-[(dodecylthiocarbamate)thio]propionic acid dissolved in cyclohexanone dropwise. Stir and react at 67℃ for 2.7h, keep warm for 4h, cool to room temperature and discharge to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion.

[0063] Step 4: 28.3g of ethanol solution containing 100mg / L copper ions and 23.7g of polyurethane acrylate emulsion modified with multi-walled carbon nanotubes were continuously stirred at room temperature for 24h to obtain a self-healing elastomer emulsion with interaction between metal coordination bonds and dynamic covalent bonds.

[0064] Step 5: Pour the self-healing elastomer solution with metal coordination bonds and dynamic covalent bonds into a polytetrafluoroethylene film mold, dry at room temperature for 3 days, and then use a vacuum pump coating machine to lay the viscous product into a film to obtain a smooth and flat film, which is the polyurethane acrylate elastomer.

[0065] Example 4

[0066] This embodiment 4 provides a method for preparing a polyurethane acrylate elastomer, including the following steps:

[0067] Step 1: 7.8g of carboxylated multi-walled carbon nanotubes, 29.4g of hydroxypropyl acrylate, 0.96g of hydroquinone, 14.7g of anhydrous sodium sulfate, and 49.5g of methyl isoamyl ketone were ultrasonicated at room temperature and 98kHz for 0.9h under N2 protection. Then, the temperature was raised to 100℃ and stirred at a constant temperature for 24h. 146g of anhydrous ethanol was added for dilution. The mixture was filtered through a 0.22μm polyvinylidene fluoride filter membrane. The filter cake was washed three times with deionized water. The resulting filter cake was vacuum dried at 50℃ for 24h to obtain grafted double bond functionalized multi-walled carbon nanotubes.

[0068] Step 2: 24g of dried isoflurane diisocyanate, 44g of 1,4-butanediol adipic acid ester monomer, and 34g of toluene were mixed evenly at 80°C under N2 protection. 0.46g of dibutyltin dilaurate was added and reacted for 0.9h. 2.07g of bis(2-hydroxyethyl) disulfide was added and reacted for 0.9h. Then, 0.95g of 5,10,15,20-tetra(4-aminophenyl)porphyrin was added and reacted for 0.9h. The reaction was maintained at this temperature for 2.9h. The temperature was then lowered to 60°C, 38g of toluene was added, and 7.4g of hydroxyethyl acrylate was added to obtain a polyurethane emulsion with double bonds capped.

[0069] Step 3: Mix 37.6g of double-bond-terminated polyurethane solution, 5.8g of butyl acrylate, 4.7g of grafted double-bond functionalized multi-walled carbon nanotubes, and 24.6g of toluene under N2 protection. Add 14.8g of 1% 2-methyl-2-[(dodecylthiocarbamate)thio]propionic acid dissolved in toluene dropwise. Stir and react at 69℃ for 2.9h, keep warm for 4h, cool to room temperature and discharge to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion.

[0070] Step 4: 29.8g of ethanol solution containing 100mg / L manganese ions and 24.8g of polyurethane acrylate emulsion modified with multi-walled carbon nanotubes were continuously stirred at room temperature for 24h to obtain a self-healing elastomer emulsion with interaction between metal coordination bonds and dynamic covalent bonds.

[0071] Step 5: Pour the self-healing elastomer solution with metal coordination bonds and dynamic covalent bonds into a polytetrafluoroethylene film mold, dry at room temperature for 3 days, and then use a vacuum pump coating machine to lay the viscous product into a film to obtain a smooth and flat film, which is the polyurethane acrylate elastomer.

[0072] Comparative Example 1

[0073] In Comparative Example 1, except that no grafted double bond functionalized multi-walled carbon nanotubes were prepared and used, the other operations were the same as in Example 1. The detailed process will not be repeated here.

[0074] Comparative Example 2

[0075] In Comparative Example 2, except that diethylthiuram dihydroxydisulfide was not added, the other operations were the same as in Example 1. The detailed process will not be repeated here.

[0076] Comparative Example 3

[0077] In Comparative Example 3, except that 5,10,15,20-tetra(4-hydroxyphenyl)porphyrin was not added, the other operations were the same as in Example 1, and the detailed process will not be repeated here.

[0078] Comparative Example 4

[0079] In Comparative Example 4, 1% azobisisobutyronitrile dissolved in 12.5g of ethyl acetate was used to replace dithiobenzoic acid-2-cyanoisopropyl ester. Other operations were the same as in Example 1, and detailed procedures will not be repeated here.

[0080] Performance testing:

[0081] The products prepared in Examples 1-4 and Comparative Examples 1-4 of this invention were subjected to molecular weight testing, mechanical property testing, and self-healing property testing.

[0082] (1) Molecular weight determination: The relative molecular mass and PDI were determined using a Shimadzu aqueous gel permeation chromatography (GPC) instrument. The GPC instrument was calibrated using a PEG standard polymer, and the weight-average molecular weight and PDI of the polymer were determined using the calibration curve.

[0083] (2) Mechanical property test: The test temperature is 25℃ and the tensile rate is 500mm / min. At least 5 specimens are tested in each group, and the average value of tensile strength and elongation at break of each group of test specimens is taken.

[0084] (3) Self-healing performance test: The tensile specimen was cut from the middle with a blade and then tightly joined together. The cut specimen was irradiated with visible light at room temperature for 12h and 24h and with ultraviolet light (wavelength 230-380nm) for 0.5h and 1h respectively to perform self-healing. The ratio of tensile strength before and after fracture was used to characterize the corresponding self-healing efficiency.

[0085] Test results:

[0086] The molecular weight, mechanical properties, and self-healing properties of the films prepared in Examples 1-4 and Comparative Examples 1-4 are listed in Table 1.

[0087] Table 1 Test results of the examples and comparative examples

[0088]

[0089]

[0090] As shown in the performance test results in Table 1 above, the molecular weight of the polyurethane acrylate elastomers prepared in Examples 1-4 is between 62,820 and 64,430, and the PDI is between 1 and 2, indicating a controllable molecular weight. When the thin-film polyurethane acrylate elastomer breaks, the tightly joined films after breakage can achieve a self-healing efficiency of 85.2% to 86.8% after being irradiated under visible light for 12 to 24 hours. After being irradiated under ultraviolet light for 0.5 to 1 hour, the self-healing efficiency can reach 100%. The elastomer also has a tensile strength of up to 46.6 to 58.6 MPa and an elongation at break of 1263% to 1585%, exhibiting excellent mechanical properties and self-healing performance.

[0091] It should be noted that, as can be seen from Example 1 and Comparative Example 1, the introduction of grafted double-bond functionalized multi-walled carbon nanotubes into the polyurethane acrylate elastomer described in Example 1 can achieve chemical bonding and effectively improve the mechanical properties of the film; as can be seen from Example 1, Comparative Example 2 and Comparative Example 3, the introduction of disulfide bonds (dynamic covalent bonds) and porphyrin metal coordination bonds into the elastomer is a key factor in achieving the self-healing properties of the elastomer film; as can be seen from Example 1 and Comparative Example 4, the polymer obtained by reversible addition-fragmentation chain transfer radical polymerization (RAFT) technology has a narrower molecular weight distribution and better mechanical properties compared with conventional free radical copolymerization.

[0092] The polyurethane acrylate elastomer, its preparation method, and its applications, as described in this invention, firstly involve esterification of carboxylated multi-walled carbon nanotubes with hydroxypropyl acrylate to obtain grafted double-bond functionalized multi-walled carbon nanotubes. Secondly, a nucleophilic addition reaction is performed between a diisocyanate monomer and a polydiol monomer, followed by the addition of hydroxyethyl acrylate to introduce double bonds, resulting in a double-bond-terminated polyurethane emulsion. Then, the double-bond-terminated polyurethane emulsion is reacted with butyl acrylate and the grafted double-bond functionalized multi-walled carbon nanotubes via reversible addition-fragmentation chain transfer radical polymerization to obtain a multi-walled carbon nanotube-modified polyurethane acrylate. Finally, coordinated metal ions are introduced into the polymer molecular chain, and after drying, a self-healing elastomer with interaction between metal coordination bonds and dynamic covalent bonds is obtained. This elastomer possesses controllable molecular weight, excellent mechanical strength and toughness, and self-healing characteristics. This material has potential applications in surface coating protection, biomedical materials, flexible wearable electronics, lithium batteries, and aerospace.

[0093] The above embodiments are merely one of the implementation methods for achieving the technical solution of the present invention. The scope of protection claimed by the present invention is not limited to this embodiment, but also includes any variations, substitutions and other implementation methods that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention.

Claims

1. A method for preparing a polyurethane acrylate elastomer, characterized in that, include: Carboxylated multi-walled carbon nanotubes were esterified with hydroxypropyl acrylate to obtain grafted double bond functionalized multi-walled carbon nanotubes. A polyurethane emulsion with double bond end capping was obtained by nucleophilic addition reaction of diisocyanate monomer and polydiol monomer, followed by addition of hydroxyethyl acrylate to introduce double bonds. Using the double-bond-terminated polyurethane emulsion, butyl acrylate, and the grafted double-bond functionalized multi-walled carbon nanotubes, a multi-walled carbon nanotube-modified polyurethane acrylate emulsion was obtained by reversible addition-bond-fracture transfer radical polymerization. Coordinated metal ions are introduced into the polyurethane acrylate emulsion modified with multi-walled carbon nanotubes, and then dried to obtain the polyurethane acrylate elastomer. The process of obtaining a double-bonded polyurethane emulsion by nucleophilic addition reaction of diisocyanate monomers with polydiol monomers, followed by the addition of hydroxyethyl acrylate to introduce double bonds, is as follows: Diisocyanate monomer, polydiol monomer and organic solvent are mixed, and dibutyltin dilaurate is added to react. Then chain extender and crosslinking agent are added to react. After that, organic solvent and hydroxyethyl acrylate are added to obtain the double bond-terminated polyurethane emulsion. The chain extender is one of diethylthiuram dihydroxydisulfide and bis(2-hydroxyethyl) disulfide; the crosslinking agent is one of 5,10,15,20-tetra(4-hydroxyphenyl)porphyrin and 5,10,15,20-tetra(4-aminophenyl)porphyrin.

2. The method for preparing a polyurethane acrylate elastomer according to claim 1, characterized in that, The process of obtaining grafted double-bond functionalized multi-walled carbon nanotubes by esterification with carboxylated multi-walled carbon nanotubes and hydroxypropyl acrylate is as follows: Carboxylated multi-walled carbon nanotubes, hydroxypropyl acrylate, hydroquinone, anhydrous sodium sulfate, and methyl isoamyl ketone were ultrasonicated at room temperature under nitrogen protection; then the temperature was raised to a preset temperature and stirred at that preset temperature; then anhydrous ethanol was added for dilution, and the mixture was filtered to obtain a filter cake; the filter cake was washed and dried to obtain the grafted double bond functionalized multi-walled carbon nanotubes.

3. The method for preparing a polyurethane acrylate elastomer according to claim 2, characterized in that, The mass ratio of carboxylated multi-walled carbon nanotubes, hydroxypropyl acrylate, hydroquinone, anhydrous sodium sulfate, and methyl isoamyl ketone is (5~8):(20~30):(0.5~1):(10~15):(40~50).

4. The method for preparing a polyurethane acrylate elastomer according to claim 1, characterized in that, The diisocyanate monomer is one of isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the polydiol monomer is one of polycaprolactone diol, polytetrahydrofuran ether diol, and poly(1- and 4-butanediol) adipate diol.

5. The method for preparing a polyurethane acrylate elastomer according to claim 1, characterized in that, The process of obtaining a multi-walled carbon nanotube-modified polyurethane acrylate emulsion via reversible addition-bond cleavage transfer radical polymerization using the double-bond-terminated polyurethane emulsion, butyl acrylate, and the grafted double-bond functionalized multi-walled carbon nanotubes is as follows: The double-bond-terminated polyurethane emulsion, butyl acrylate, the grafted double-bond functionalized multi-walled carbon nanotubes, and an organic solvent are mixed evenly. Then, RAFT chain transfer agent is added and the mixture is stirred and reacted. The mixture is kept warm and cooled to room temperature before being discharged to obtain a multi-walled carbon nanotube-modified polyurethane acrylate emulsion.

6. The method for preparing a polyurethane acrylate elastomer according to claim 1, characterized in that, The process of introducing coordinated metal ions into the multi-walled carbon nanotube-modified polyurethane acrylate emulsion and drying it to obtain the polyurethane acrylate elastomer is as follows: An ethanol solution of metal ions is mixed with the polyurethane acrylate emulsion modified with multi-walled carbon nanotubes, and the mixture is stirred continuously to obtain a self-healing elastomer emulsion. The self-healing elastomer emulsion is then dried to obtain the polyurethane acrylate elastomer.

7. The method for preparing a polyurethane acrylate elastomer according to claim 6, characterized in that, The metal ion is one of the following: iron ion, nickel ion, copper ion, cobalt ion, manganese ion, and zinc ion.

8. A polyurethane acrylate elastomer, characterized in that, It is prepared using the preparation method of a polyurethane acrylate elastomer as described in any one of claims 1-7; The polyurethane acrylate elastomer has a molecular weight of 62,820 to 64,430. When the thin-film polyurethane acrylate elastomer breaks, it can achieve a self-healing efficiency of 85.2% to 86.8% under visible light irradiation for 12 to 24 hours, and a self-healing efficiency of 100% under ultraviolet light irradiation for 0.5 to 1 hour. The tensile strength of the polyurethane acrylate elastomer is 46.6 to 58.6 MPa, and the elongation at break is 1263% to 1585%.

9. The application of the polyurethane acrylate elastomer as described in claim 8, characterized in that, Applications as self-healing, stretchable conductive devices.

Citation Information

Patent Citations

  • High-toughness self-repairing supramolecular polyurethane elastomer based on thiolactone chemistry and preparation method of high-toughness self-repairing supramolecular polyurethane elastomer

    CN116217889A

  • Urethane-acrylate / nano-metal composite emulsion and preparation method thereof

    CN116284614A